Flexible Neural Interfaces Based on 3D PEDOT:PSS Micropillar Arrays. Issue 25 (11th July 2022) - Lunghi, Alice; Mariano, Anna; Bianchi, Michele; Dinger, Nikita Bhupesh; Murgia, Mauro; Rondanina, Eliana; Toma, Andrea; Greco, Pierpaolo; Di Lauro, Michele; Santoro, Francesca; Fadiga, Luciano; Biscarini, Fabio
Abstract: Multi‐electrode arrays with 3D micropillars allow the recording of electrophysiological signals in vitro with higher precision and signal‐to‐noise ratio than planar arrays. This is the result of the tight interaction between the 3D electrode and the cell membrane. Most 3D electrodes are manufactured on rigid substrates and their integration on flexible substrates is largely unexplored. Here, a straightforward approach is presented for fabricating soft interfaces featuring 3D poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) micropillars on a soft flexible substrate made of polydimethylsiloxane (PDMS). Large‐area isotropic arrays of PEDOT:PSS micropillars with tailored geometric area, surface properties, and electrochemical characteristics are fabricated via a combination of soft‐lithography and electrodeposition. A 60% increase in capacitance is achieved for high density micropillars compared to planar electrodes and this is found to be correlated with the increased electroactive surface area. Furthermore, 3D PEDOT:PSS micropillars support adhesion, growth and differentiation of SH‐SY5Y cells, and influence the direction of neurite outgrowth. Finally, by virtue of their elasticity, soft micropillars act as excellent anchoring loci for elongating neurites, facilitating their bending and twisting around the micropillar, increasing the number of contact points between the cells and the electrode, a key requirement to obtain high performance neural interfaces. Abstract : Isotropic arrays of low‐aspect ratio PEDOT:PSS micropillars with tailored geometric area, surface properties, and electrochemical characteristics are fabricated via a combination of soft‐lithography and electrodeposition. Such conductive microstructured neural interface supports adhesion, growth and differentiation of SH‐SY5Y cells, as well as influencing the direction of neurite outgrowth.